2021
DOI: 10.1055/s-0041-1729464
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Analysis of the Anatomical Variants in Genicular Artery Embolization

Abstract: Purpose: Genicular artery embolization (GAE) has been proposed as a novel technique to treat painful synovitis related to osteoarthritis. An in-depth understanding of the genicular arterial anatomy is crucial to achieve technical success and avoid nontarget-related complications. Given the lack of previous angiographic description, the present study analyzes genicular arterial anatomy and proposes an angiographic classification system. Materials and Methods: Angiographic findings from 41 GAEs performed during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 20 publications
(23 reference statements)
0
24
0
Order By: Relevance
“…GAE requires a fundamental knowledge of knee vascular anatomy, along with its variations, for effectively and safely identifying the embolizing target [ 37 , 38 ]. Three main vessels provide the vascular supply to the knee.…”
Section: Global Prevalence Natural History Risk Factors Pathophysiolo...mentioning
confidence: 99%
See 2 more Smart Citations
“…GAE requires a fundamental knowledge of knee vascular anatomy, along with its variations, for effectively and safely identifying the embolizing target [ 37 , 38 ]. Three main vessels provide the vascular supply to the knee.…”
Section: Global Prevalence Natural History Risk Factors Pathophysiolo...mentioning
confidence: 99%
“…Angiographic studies also correlate with these cadaveric findings. In a recent study by Bagla et al, angiographic findings from 39 GAE procedures showed anatomical variations of the medial and lateral genicular arteries [ 38 ]. Three medial branches (DGA, SMGA, and IMGA) and three lateral branches (SLGA, ILGA, and ATRA) were analyzed.…”
Section: Global Prevalence Natural History Risk Factors Pathophysiolo...mentioning
confidence: 99%
See 1 more Smart Citation
“…An angiographic classification for the genicular vascular anatomy was proposed recently: medially-M1 (3/3 arteries present) versus M2 (2/3 arteries present), laterally-L1 (3/3 arteries present) versus L2 (2/3 arteries present). 16 Of note, the superior patellar artery and the median genicular artery were studied by Okuno et al but has not been included in any other studies given its small vessel size and limited involvement in the knee joint. When performing GAE, it is important to understand that the knee joint is a highly vascular structure with numerous arterial anastomoses that can potentially lead to nontarget embolization.…”
mentioning
confidence: 99%
“…6,7 This principle has been successfully applied to knee pain secondary to osteoarthritis (OA), as genicular artery embolization (GAE) was found to significantly reduce pain and increase function in patients with mild to moderate OA. [8][9][10][11][12][13][14][15][16] The success of GAE for OA has led to the application of musculoskeletal embolization to other inflammatory conditions like adhesive capsulitis (AC), lateral epicondylitis (LE), and other isolated cases of tendinitis.…”
mentioning
confidence: 99%